Family Instability and Child Well-Being - Fomby, Paula; Cherlin, Andrew J. (American Sociological Review, 2007)
Children who experience multiple transitions in family structure may face worse developmental outcomes than children raised in stable, two-parent families, and perhaps even worse than children raised in stable, single-parent families—a point denoted in much prior research. Multiple transitions and negative child outcomes, however, may be associated through common causal factors such as parents' antecedent behaviors and attributes. Using a nationally-representative, two-generation longitudinal survey that includes detailed information on children's behavioral and cognitive development, family history, and mothers' attributes prior to children's births, we examine these alternative hypotheses. Our results suggest that, for white children, the association between the number of family structure transitions and cognitive outcomes is largely explained by mothers' prior characteristics but that the association between the number of transitions and behavioral outcomes may be causal in part. We find no robust effects for number of transitions for black children.